2012
DOI: 10.1111/jnp.12003
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory and episodic future thinking after moderate to severe traumatic brain injury

Abstract: Converging evidence suggests that autobiographical memory and episodic future thinking share a common neurocognitive basis. Although previous research has shown that traumatic brain injury (TBI) can impair the ability to remember the personal past, episodic future thinking has not previously been systematically examined within this population. In this study, we examined the ability to remember events in the personal past and the ability to imagine possible events in the personal future in a sample of moderate‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 81 publications
(117 reference statements)
3
32
1
Order By: Relevance
“…Bach and David, 2006;Nochi, 1998;Tyerman and Humphrey, 1984). This result seems in contrast with a previous TBI study by Rasmussen and Berntsen (2014) reporting a decline in episodic details, but not in semantic details for past and future events, thus, suggesting that the semantic component of SMS was spared in TBI. It was proposed that patients' future thinking could be based on stereotypical and rigid routines, which, in turn, contributed to the behavioral inflexibility and poor goal attainment often associated with TBI.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Bach and David, 2006;Nochi, 1998;Tyerman and Humphrey, 1984). This result seems in contrast with a previous TBI study by Rasmussen and Berntsen (2014) reporting a decline in episodic details, but not in semantic details for past and future events, thus, suggesting that the semantic component of SMS was spared in TBI. It was proposed that patients' future thinking could be based on stereotypical and rigid routines, which, in turn, contributed to the behavioral inflexibility and poor goal attainment often associated with TBI.…”
Section: Discussioncontrasting
confidence: 85%
“…This deficit was independent of the difficulties in basic verbal fluency, general semantic skills and speed processing, thus seemingly arguing in favour of a global disruption of the temporally extended SMS in TBI. Simultaneous difficulties in episodic re-experiencing and episodic pre-experiencing, in keeping with our predictions, are indicative of altered mental time travel (Tulving, 2002), mirroring the profile already observed in amnesic clinical populations Hassabis et al, 2007;Maguire et al, 2010), and more recently in non-amnesic ones, such as TBI (Rasmussen and Berntsen, 2014). All these patients generally present the inability to extract sensory-perceptual details from previously experienced events, and to integrate episodic details within the appropriate scenario for future episodic simulations.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Moreover, examining the integrity of autobiographical memory more broadly may illuminate how mTBI affects the generation of autobiographical details for experiences that are less salient than the one sampled here. Some studies have demonstrated more pervasive autobiographical memory deficits in moderate to severe TBI (Piolino et al, 2007;Rasmussen & Berntsen, 2014), but little is known about autobiographical memory in mTBI.…”
Section: Discussionmentioning
confidence: 99%